Le storie degli animali nel Corano di Ahmad Bahgat: Quando gli animali prendono la parola (Altre Modernità, 2021)
In Islam-inspired literature, tales of the lives of the Prophets have always highlighted the contribution of animals, though in a subordinate role compared to that of men. The anthology Qiṣaṣ al ḥayawān fil Qur’ān (Stories of Animals in the Quran) by Egyptian author and journalist Ahmad Bahgat stands as an exception. In its sixteen tales inspired by episodes in the Quran which showcase animals involved in wonders and miracles, the main characters are the animals themselves, who tell the Quranic tale like in a first-hand diary, in the first-person and from their own point of view. For the first time light is shed on their existence, without the overshadowing of those of the men with whom they have interacted. It is thus interesting to break down the representation of animals in these stories and grasp its originality. The first part of the essay will concern the author’s sources and how they impact the narrative while the second will focus on the choice of the animal as a means of circumventing the Islamic ban on the representation of the Prophets (Islam is notoriously an iconoclastic religion), achieved by superposing the animal on the Prophet, both in body and soul. The third part will examine the animal/virtue standing as the inverted double of the man/vice and, by consequence, the removal of bias concerning some animals in Arabic-Muslim culture.